Cytisine versus varenicline for smoking cessation in New Zealand indigenous Māori: a randomized controlled trial. (4th May 2021) - Walker, Natalie; Smith, Barry; Barnes, Joanne; Verbiest, Marjolein; Parag, Varsha; Pokhrel, Subhash; Wharakura, Mary‐Kaye; Lees, Tina; Cubillos Gutierrez, Huber; Jones, Brian; Bullen, Christopher
Abstract: Aim: To determine whether cytisine was at least as effective as varenicline in supporting smoking abstinence for ≥ 6 months in New Zealand indigenous Māori or whānau (extended‐family) of Māori, given the high smoking prevalence in this population. Design: Pragmatic, open‐label, randomized, community‐based non‐inferiority trial. Setting: Bay of Plenty, Tokoroa and Lakes District Health Board regions of New Zealand. Participants: Adult daily smokers who identified as Māori or whānau of Māori, were motivated to quit in the next 2 weeks, were aged ≥ 18 years and were eligible for subsidized varenicline. Recruitment used multi‐media advertising. Interventions: A total of 679 people were randomly assigned (1 : 1) to receive a prescription for 12 weeks of cytisine or varenicline, plus low‐intensity cessation behavioural support from the prescribing doctor and community stop‐smoking services or a research assistant. Day 5 of treatment was the designated quit date. Measurements: The primary outcome was carbon monoxide‐verified continuous abstinence at 6 months, analysed as intention‐to‐treat (with multiple imputation for missing data). Secondary outcomes measured at 1, 3, 6 and 12 months post‐quit date included: self‐reported continuous abstinence, 7‐day point prevalence abstinence, cigarettes per day, time to (re)lapse, adverse events, treatment adherence/compliance and acceptability, nicotine withdrawal/urge to smoke and health‐care utilization/health‐related quality of life. Findings: Verified continuous abstinence rates at 6 months post‐quit date were 12.1% (41 of 337) for cytisine versus 7.9% (27 of 342) for varenicline [risk difference 4.29%, 95% confidence interval (CI) = –0.22 to 8.79; relative risk 1.55; 95% CI = 0.97–2.46]. Sensitivity analyses confirmed that the findings were robust. Self‐reported adverse events over 6 months occurred significantly more frequently in the varenicline group (cytisine: 313 events in 111 participants; varenicline: 509 events in 138 participants, incidence rate ratio 0.56, 95% CI = 0.49–0.65, P  < 0.001) compared with the cytisine group. Common adverse events were headache, nausea and difficulty sleeping. Conclusion: A randomized controlled trial found that cytisine was at least as effective as varenicline at supporting smoking abstinence in New Zealand indigenous Māori or whānau (extended‐family) of Māori, with significantly fewer adverse events.